OVERCOMING LANGUAGE ANXIETY: PSYCHOLOGICAL APPROACHES TO BUILD CONFIDENCE IN MIDDLE SCHOOL ENGLISH LEARNERS - Zikriddinova Mutabar Faxriddin qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: Language anxiety is one of the most common psychological barriers that hinders middle school students from actively participating in English language learning. It often manifests as fear of making mistakes, speaking in front of peers, or being judged by others, leading to low confidence and reduced performance. This article explores various psychological approaches to overcoming language anxiety and building self-confidence among English learners. The study emphasizes the importance of creating a supportive classroom environment, implementing relaxation techniques, promoting positive feedback, and using collaborative learning strategies. By addressing emotional factors alongside linguistic competence, teachers can help students develop confidence, motivation, and resilience in learning English.